Music and Adolescent Behavior - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1989)
The role of music in the lives of adolescents and the use of music preferences as clues to the emotional and mental health of adolescents is reviewed from the Group on Science and Technology, American Medical Association, Chicago, IL.